Feeding profile of infant and young children with stunting in Kuantan, Pahang - Musa, Noraini; Pasi, Hafizah; Kamaruzaman, Nor Azam (2021)
Stunting refers to low height for age primarily due to chronic under nutrition. It is the most prevalent form of malnutrition in the under-five population, both globally and locally. This study aims to describe the feeding profiles of infant and young children who were diagnosed with stunting. It revealed that 1 in 4 of the stunted children was non-exclusively breastfed, while feeding problem was prevalent among them. 25% of children were non-exclusively breastfed. 40% received inadequate meal frequency, 57.5% inadequate meal amount, 7.5% inadequate meal variety and 15% were not actively fed. Recognition and intervention of feeding problem are critical to improve the overall health and nutritional status of under five children with stunting.